2010
DOI: 10.1007/s10552-010-9522-9
|View full text |Cite
|
Sign up to set email alerts
|

Australian women’s awareness of breast cancer symptoms and responses to potential symptoms

Abstract: Health promotion efforts need to continue to aim at increasing community understanding of potential breast cancer symptoms and encouraging women to act on potential symptoms by seeking medical advice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
4
14
1
Order By: Relevance
“…If a woman was not available in all visits or declined to participate in the study, the household was jumped and the immediate next household in the sampling frame was considered. Pretested, semi-structured questionnaire adapted from studies done in Nigeria and Iran [15,16] was used for the data collection. Data were collected by five health professionals specifically trained for this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If a woman was not available in all visits or declined to participate in the study, the household was jumped and the immediate next household in the sampling frame was considered. Pretested, semi-structured questionnaire adapted from studies done in Nigeria and Iran [15,16] was used for the data collection. Data were collected by five health professionals specifically trained for this study.…”
Section: Methodsmentioning
confidence: 99%
“…More than 90% of cases of breast cancer can be detected by women themselves, stressing the importance of breast self-examination (BSE) as the key breast cancer detection mechanism [9]. The problem is that poor awareness of breast cancer symptoms has usually been associated with patient delay in seeking help resulting in reduced survival, more aggressive and fewer treatment options [10].…”
Section: Introductionmentioning
confidence: 99%
“…This has led to several studies investigating the actual problem by way of studying breast cancer awareness (Khokhar, 2009;Al-Dubai et al, 2011;Kanaga et al, 2011;Gurdal et al, 2012;Wu et al, 2012;Yoo et al, 2012;Donnelly et al, 2013;Norlaili et al, 2013;Radi, 2013;Liu et al, 2014;Sathian et al, 2014;Miyawaki, Shibata et al, 2014;Tazhibi and Feizi, 2014). Most studies have found that the awareness of breast cancer in developing countries was weak compared with developed countries (Jones et al, 2010;Kwok et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge regarding breast cancer has been shown to be better among the more educated, and is generally satisfactory in developed countries [6,7]. Awareness and health seeking practices have been shown to be poor in many developing countries, necessitating the need for proper awareness programs [8,9].…”
Section: Introductionmentioning
confidence: 99%